Identifikasi Dan Kelimpahan Jenis Kepiting Bakau (Scylla sp) Di Sungai Antan Desa Telak Kabupaten Bangka Barat - Rafzan Miftaza Fahzeri; Fika Dewi Pratiwi; Andi Gustomi (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2023)
Telak Village is an area with a large area of mangrove forest, with flora and fauna biodiversity in it. One type of crustacean that has high economic value is mangrove crab. This study aims to identify the types of mud crabs, analyze the abundance of mud crab species and analyze the relationship between the abundance of mud crab species and environmental parameters. This research was conducted in July – August 2022 at Sungai Antan, Telak Village. The research method used is purposive sampling method. Data collection is divided into 3 stations, where each station has 1 line transect with a length of 100 meters with an interval of 20 meters between plots (folding trap). The results of the study obtained 2 species of mud crabs namely Scylla tranquebarica and Scylla serrata. The highest abundance of mud crabs of Scylla serrata was at station 1, namely 0.07 individuals/m² and the highest abundance of mud crabs of Scylla tranquebarica was at station 2, namely 0.22 individuals/m². this indicates, there is ecological pressure in an ecosystem which results in few mud crabs being found. The sex of mud crabs that were mostly found were male mud crabs totaling 36 individuals and female mangrove crabs totaling 25 individuals with a total of 61 individuals. The abundance of mud crabs Scylla serrata is closely related to the dust fraction, while the abundance of mud crabs Scylla tranquebarica is closely related to salinity.